EMPLOYEE PERFORMANCE MANAGEMENT STRATEGY THROUGH JOB SATISFACTION MODERATED BY WORK MOTIVATION IN THE ASSOCIATION OF INDONESIAN SHOPPING CENTER MANAGERS IN EAST JAVA - Awan Indrawan,; Nur Sayidah,; Sri Handini, (International Journal of Social Science, 2025)
The purpose of this study is to analyze the influence of Organizational Commitment, Organizational Culture, Work Environment, Incentives, Awards, and Leadership Style on Employee Performance through Job Satisfaction and moderated by Work Motivation. This study uses a quantitative approach with a causal research type. The study population is all permanent employees at the Indonesian Shopping Center Management Association East Java, totaling 318 people. The sampling method uses Purposive Sampling and Slovin techniques so that a sample of 177 permanent employees at the Indonesian Shopping Center Management Association East Java is obtained. The data collection method uses a Questionnaire with SEM Partial Least Square data analysis techniques. The results of the study prove that Organizational Commitment, Organizational Culture, Work Environment, and Leadership Style have a significant positive effect on Employee Performance. However, Incentives and Awards do not have a significant positive effect on Employee Performance. Job Satisfaction is able to significantly mediate the relationship between Organizational Culture, Incentives, and Awards on Employee Performance. However, Job Satisfaction was unable to significantly mediate the positive relationship between Organizational Commitment, Work Environment, and Leadership Style on Employee Performance. Work Motivation was unable to significantly moderate the positive relationship between Job Satisfaction and Employee Performance.